Parasellar Chondroid Chordoma: a Case Report - B Syam Sundar Rao; Vissa Shanthi; N Mohan Rao; Bhavna G; S Swathi; Murali Mohan K (International Journal of Medical Research and Review, 2014)
Chordomas are distinct tumors which arise almost exclusively in the midline skeleton, from skull base to the sacrum. Chondroid chordoma is a rare form of chordoma with features of chordoma and chondrosarcoma arising almost at skull base. We report a case of a right parasellar chondroid chordoma in 54 years old female. Histopathology and IHC confirm the diagnosis of this case.